Revamping Climate Knowledge Products in the Postgraduate Program: Extended Effort from Revamping Knowledge Products in the Undergraduate Program - Belay, Berhanu; Amha, Yosef; Ambaw, Gebermedihin; Demissie, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate variability and change are likely to contribute significantly to the food security challenges of millions of Ethiopians. To address this issue, efforts are being made to enhance climate education and raise awareness among the next-generation workforce, equipping them with climate knowledge and enabling them to develop resilience and adaptive capacity. One effective approach to ensure the curriculum remains dynamic is through a process called revamping, which involves integrating relevant content into the existing curriculum. The decision to update the curriculum using a revamping approach lies with the instructors, who have the flexibility to determine the most suitable strategies based on the prevailing situation and available opportunities. Revamping has been chosen as a quick-win approach in the context of updating curricula. Notably, the successful revamping of the climate Knowledge Products (CKP) in undergraduate (UG) programs, guided by public universities and the Accelerating Impacts of CGIAR Climate Research for Africa project (AICCRA) (Berhanu et al., 2023), as well as the integration of community-based breeding programs in collaboration with the International Center for Agricultural Research in the Dry Areas (ICARDA) and public universities (Berhanu et al., 2022), has paved the way for revamping CKP into postgraduate (PG) programs. Drawing lessons from the UG revamping experience, the integration of CKP into PG programs has become necessary. As a result, six universities have revamped CKP in 32 PG programs, and the updated curricula are now being utilized for teaching and learning purposes. This intervention has benefitted more than 304 students annually. Recognizing that science and technology are constantly evolving, extending these revamping experiences to other fields has become imperative, irrespective of the discipline. This ensures that the curricula remain up to date, preparing graduates with the current state of knowledge in their respective fields.